Analisis Efektifitas Pengembangan Lembar Kerja Peserta Didik Berbantuan PhET Interactive Simulations untuk Meningkatkan Creative Thinking Skills melalui Model Research Based Learning pada Materi Momentum dan Impuls - Chuznul Chotimah; Festiyed Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2020)
The purpose of this study was to describe the effectiveness of LKPD assisted by Phet Interactive Simulations in the Research Based Learning model to improve the Creative Thinking Skills of high school students. The research method used is descriptive method using quantitative data sheet LKPD effectiveness seen from students' Creative Thinking Skills. The results of the effectiveness of Creative Thinking Skills obtained 81.17% with the effective category.